Effect Of Blast Design On Particle Breakage At Imerys Minerals Malaysia Sdn. Bhd. Simpang Pulai, Ipoh - Rodzali, Mohammad Aidil (Universiti Sains Malaysia, 2017)
The present study aims to investigate the relationship the blast design and particle breakage on how the blast design effects the fragmentation of rock in term of obtaining the optimum fragmentation. The fragmentation of rock significantly affects the performance of loading, hauling and comminution process. Based on the Point Load Test, rocks in all blast sessions were classified as medium strength rock. Imerys Minerals Malaysia adopted staggered pattern for blast hole pattern which produces much more uniform distribution of explosive energy rather than square and rectangular pattern. Ammonium Nitrate Fuel Oil (ANFO) was selected as a primary explosive for each session of blasting instead of Bulk Emission although Bulk Emission has a good water resistance. The data obtained from the study indicate that the average percentage passing for size of 800mm (feed opening for jaw crusher) in all blast sessions was 72.83% which means that the remaining percentage required secondary breakage. The average value of uniformity index for all blast sessions was 1.63 and the average value of D50 was 527.18mm. The average of maximum size rock fragmentation for all blast sessions was 2220.54mm. The rock fragmentation achieved during the blasting operation was far away from achieving optimum fragmentation.